Systemic immune-inflammation index and all-cause and cause-specific mortality in sarcopenia: a study from National Health and Nutrition Examination Survey 1999-2018 - Zeng, Qing-Yue; Qin, Yu; Shi, Yi; Mu, Xing-Yu; Huang, Shi-Jun; Yang, Yu-Hao; Liu, Si-Min; An, Zhen-Mei; Li, Shuang-Qing (Frontiers in Immunology, 2024)
Background Sarcopenia, common in the elderly, often linked to chronic diseases, correlates with inflammation.The association between SII and mortality in sarcopenia patients is underexplored, this study investigates this relationship in a U.S. adult cohort. Methods We analyzed 1999–2018 NHANES data, focusing on 2,974 adults with sarcopenia. Mortality outcomes were determined by linking to National Death Index (NDI) records up to December 31, 2019. Using a weighted sampling design, participants were grouped into three groups by the Systemic Immune-Inflammation Index (SII). We used Cox regression models, adjusting for demographic and clinical variables, to explore SII’s association with all-cause and cause-specific mortality in sarcopenia, performing sensitivity analyses for robustness. Results Over a median follow-up of 9.2 years, 829 deaths occurred. Kaplan-Meier analysis showed significant survival differences across SII groups. The highest SII group showed higher hazard ratios (HRs) for all-cause and cause-specific mortality in both crude and adjusted models. The highest SII group had a higher HR for all-cause(1.57, 1.25–1.98), cardiovascular(1.61, 1.00–2.58), cancer(2.13, 1.32–3.44), and respiratory disease mortality(3.21, 1.66–6.19) in fully adjusted models. Subgroup analyses revealed SII’s association with all-cause mortality across various demographics, including age, gender, and presence of diabetes or cardiovascular disease. Sensitivity analyses, excluding participants with cardiovascular diseases, those who died within two years of follow-up, or those under 45 years of age, largely reflected these results, with the highest SII group consistently demonstrating higher HRs for all types of mortality in both unadjusted and adjusted models. Conclusion Our study is the first to demonstrate a significant relationship between SII and increased mortality risks in a sarcopenia population.